Experimental results of polarimetric detection schemes for DVB‐T‐based passive radar. Issue 6 (9th May 2017) - Filippini, Francesca; Colone, Fabiola; Cristallini, Diego; Bournaka, Georgia
Abstract : This study investigates the potential advantages conveyed by the exploitation of polarimetric diversity in Passive Coherent Location (PCL) system exploiting Digital Video Broadcasting – Terrestrial (DVB‐T) signals. To this purpose, different polarimetric detection schemes are considered that jointly exploit the signals collected at different receiving channels characterised by differently polarised antennas. A performance analysis has been carried out using experimental data collected by a passive radar system developed by Fraunhofer, namely PARASOL. This PCL system employs two orthogonal linearly polarised receiving channels (horizontal and vertical). The results obtained against cooperative targets demonstrate that a Polarimetric Generalised Likelihood Ratio Test (P‐GLRT) detection scheme provides a remarkable improvement in terms of target detection capability as compared to the single‐polarisation operation and the non‐coherent integration of the results obtained at the available polarimetric channels.